3.05 kW monolithic fiber laser oscillator with simultaneous optimizations of stimulated Raman scattering and transverse mode instability. (8th January 2018) - Yang, Baolai; Zhang, Hanwei; Shi, Chen; Tao, Rumao; Su, Rongtao; Ma, Pengfei; Wang, Xiaolin; Zhou, Pu; Xu, Xiaojun; Lu, Qisheng
Abstract: We report a high power monolithic ytterbium-doped fiber laser oscillator with an output power of 3.05 kW, which is achieved by simultaneous optimizations of the stimulated Raman scattering (SRS) and transverse mode instability (TMI). The optimizations of the SRS are designed and utilized in the construction of the fiber laser oscillator, while the TMI threshold is optimized with the study of the dependence of TMI threshold on the pump distribution. In the fiber laser oscillator, the TMI threshold is enhanced by ∼30% when the counter-pump scheme is employed instead of the co-pump scheme. By applying bidirectional-pump scheme and appropriately distributing the pump power, the TMI threshold is further enhanced and the monolithic fiber laser oscillator achieves an output power of 3.05 kW with near diffraction limited beam quality.